Auditors as intermediaries in the endogenization of an accounting standard: The case of IFRS 15 within the telecom industry - Kohler, Hervé; Pochet, Christine; Le Manh, Anne (Accounting, Organizations and Society, 2021)
This study is about auditors’ role as regulatory intermediaries in the international accounting standard-setting process. Drawing from the socio-legal literature, we use a theoretical framework combining the Regulator-Intermediary-Target (RIT) model and the legal endogeneity theory that sheds light on auditors’ role in fostering the emergence of an agreed-upon meaning of a standard. While standards are open to different possible interpretations at implementation stage, we argue that standard-setting is a critical step at which a significant part of standard’s meaning is locked in. Hence the importance of discussions over the substance and wording of standards for parties involved in the due process. We investigate auditors’ support to their clients engaging in such discussions leading to the co-construction of the standard’s meaning and thus to the potential endogenization of the standard. For this purpose, the IASB due process is conceptualized as a regulatory conversation (Black, 2002). We use a single case study carried out in the office of one large accounting firm. Our examination focuses on discussions between the IASB and telecommunications industry representatives around the draft IFRS 15 on revenue recognition, as depicted by the latter’s auditors. We find that auditors from the firm’s in-house consulting network play a pivotal role in assisting field auditors and their clients engaging with the IASB while preserving the firm’s reputation. Taken as a whole, our findings suggest that auditors played a pivotal role as intermediaries between the IASB (the regulator) and the targets (Telco firms) and as such contributed to the partial endogenization of the draft IFRS 15. We discuss the implications of our findings for conceptualizing auditor’s role in accounting standard-setting.